Utilizing a Restricted Access e-Learning Platform for Reform, Equity, and Self-development in Correctional Facilities - Yannis C. Stamatiou; Constantinos Halkiopoulos; Athanasios Giannoulis; Hera Antonopoulou (Emerging Science Journal, 2022)
Objectives: The goal of this paper is to address the issues that arose because of the exclusion of law offenders in the Greek Correctional Institutions from second chance education during the COVID-19 pandemic. During this period, the offenders were deprived of their right to equal access to second-chance education since the pandemics blocked mobility and close contact with teaching personnel. Methods/Analysis: In this paper, we propose a framework based on the Technology Acceptance Model (TAM) that will be deployed to evaluate the acceptance of the CILMS by the learners in Correctional Institutions. We describe a methodology and a set of hypotheses that can reveal the intention of learners to use the system based on several factors, such as trust, perception of privacy, perception of usefulness, and perception of self-efficacy. Findings: We suggest that eLearning and limited Internet access should be added to the list of fundamental human rights for CI detainees as well, in order to counteract their separation from physical society. Inmates are still individuals. In fact, they should be placed in solitary confinement as prescribed by the law. Novelty/Improvement:This viewpoint has been demonstrated with the development and evaluation of acceptance by inmates through the TAM technology acceptance methodology, as well as the proposal of a generic privacy-preserving Web information and services access model for CIs that can, at the same time, provide sufficient information access freedom while respecting the restrictions that should be imposed on such an access for CI inmates. Doi: 10.28991/ESJ-2022-SIED-017 Full Text: PDF